PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA GAME BAAMBOOZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS V SDN 43 HULONTHALANGI - Darman, Nur Masita; Kudus; Rifda Mardian Arif; Abdul Haris Panai; Gamar Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This class action research examined whether the application of the PBL model with the Baamboozle game could improve student learning outcomes in science subjects of grade V of SDN 43 Hulonthalangi. This study aimed to improve student learning outcomes on human digestive system material through the application of the PBL model with the baamboozle game. This study used 23 students in grade V as the subject. Based on the analysis, the PBL model assisted by the Baamboozle game escalated the student learning outcomes on the human digestive system material. In the first cycle, 14 students (60.9%) reached the minimum completeness standard (have not achieved the success indicator and required the 2nd cycle implementation) and increased to 19 students (82.6%) in the 2nd cycle. In conclusion, the PBL model assisted by the Baamboozle game can improve the learning outcomes of students in grade V of SDN 43 Hulonthalangi.   Keywords: learning outcomes, PBL model, baamboozle game